Magnesium‐Catalyzed Hydroboration of Terminal and Internal Alkynes. Issue 21 (12th April 2019) - Magre, Marc; Maity, Bholanath; Falconnet, Alban; Cavallo, Luigi; Rueping, Magnus
Abstract: A magnesium‐catalyzed hydroboration of alkynes providing good yields and selectivities for a wide range of terminal and symmetrical and unsymmetrical internal alkynes has been developed. The compatibility with many functional groups makes this magnesium catalyzed procedure attractive for late stage functionalization. Experimental mechanistic investigations and DFT calculations reveal insights into the reaction mechanism of the magnesium catalyzed protocol. Abstract : MgBu2 proved to be an efficient catalyst for the hydroboration of terminal and internal alkynes, achieving good yields and selectivities. The compatibility with many functional groups makes the Mg‐catalyzed hydroboration of alkynes very attractive as a late stage functionalization procedure. Moreover, experimental investigations together with DFT calculations provide insight into the reaction mechanism.